Protein arrangement factor: a new photosynthetic parameter characterizing the organization of thylakoid membrane proteins - Konert, Grzegorz; Steinbach, Gabor; Canonico, Myriam; Kaňa, Radek (Physiologia plantarum, 2019)
A proper spatial distribution of photosynthetic pigment-protein complexes - PPCs (photosystems, light-harvesting antennas) is crucial for photosynthesis. In plants, photosystems I and II (PSI and PSII) are heterogeneously distributed between granal and stromal thylakoids. Here we have described similar heterogeneity in the PSI, PSII and phycobilisomes (PBSs) distribution in cyanobacteria thylakoids into microdomains by applying a new image processing method suitable for the Synechocystis sp. PCC6803 strain with yellow fluorescent protein-tagged PSI. The new image processing method is able to analyze the fluorescence ratios of PPCs on a single-cell level, pixel per pixel. Each cell pixel is plotted in CIE1931 color space by forming a pixel-color distribution of the cell. The most common position in CIE1931 is then defined as protein arrangement (PA) factor with xy coordinates. The PA-factor represents the most abundant fluorescence ratio of PSI/PSII/PBS, the 'mode color' of studied cell. We proved that a shift of the PA-factor from the center of the cell-pixel distribution (the 'median' cell color) is an indicator of the presence of special subcellular microdomain(s) with a unique PSI/PSII/PBS fluorescence ratio in comparison to other parts of the cell. Furthermore, during a 6-h high-light (HL) treatment, 'median' and 'mode' color (PA-factor) of the cell changed similarly on the population level, indicating that such microdomains with unique PSI/PSII/PBS fluorescence were not formed during HL (i.e. fluorescence changed equally in the whole cell). However, the PA-factor was very sensitive in characterizing the fluorescence ratios of PSI/PSII/PBS in cyanobacterial cells during HL by depicting a 4-phase acclimation to HL, and their physiological interpretation has been discussed.
Keywords: Photosystem I Protein Complex; Photosystem II Protein Complex; Thylakoid Membrane Proteins; proteiny tylakoidní membrány; fykobilizomy; fotosystém I (proteinový komplex); Photosynthesis; fotosystém II (proteinový komplex); Phycobilisomes; fotosyntéza